Color Perception and Preference Among Older Map Readers - Gavin, Christopher M. (My University, 2012)
Research outside of cartography suggests that color perception changes as one ages. The goal of this study is both to explore and to acquire a better understanding of how individuals of advanced ages understand and perceive information depicted on color maps. In particular, this research aims to answer four main questions: 1) How well do members of older age groups understand choropleth maps, and do they differ from other age groups? 2) Do the gender or color vision abilities of older individuals impact their ability to interpret the maps? Do these also affect their opinions regarding the aesthetic appeal of the colors? 3) Do different color schemes allow older individuals to interpret the information on choropleth maps more quickly and accurately? 4) How do older individuals rate the varying color schemes in terms of visual appeal?
Includes Color Figures, Appendices, Tables, Maps and Bibliography.
Keywords: Perception; Color; Map Reading